A 7-Years Active Pharmacovigilance Study of Adverse Drug Reactions Causing Children Admission to a Pediatric Emergency Department in Sicily - Chiara Nasso; Anna Mecchio; Michelangelo Rottura; Mariella Valenzise; Francesca Menniti-Ippolito; Paola Maria Cutroneo; Violetta Squadrito; Francesco Squadrito; Giovanni Pallio; Natasha Irrera; Vincenzo Arcoraci; Domenica Altavilla (Frontiers Media S.A., 2020)
Children represent one of the most susceptible groups to adverse drug reactions (ADRs), as a consequence of physiological growth and maturation of different organ systems. The aim of this study was to characterize the frequency, preventability and seriousness of ADRs recorded in the Pediatric Emergency Department (ED) of the University hospital of Messina, in Sicily. All the suspected adverse reactions to drugs and vaccines collected from 2012 to 2018 were selected and then analyzed. Only adverse drug reactions (ADRs) with a probable or possible causality assessment were included, according to the Naranjo Algorithm and the World Health Organization criteria; the preventability assessment using Schumock and Thornton criteria was also carried out. The Medical Dictionary for Regulatory Activities (MedDRA) was used to group ADRs. Of 75,935 admissions to the Pediatric ED, 120 were due to suspected ADRs. The rate of hospital admission due to ADRs (75.8%) was significantly greater than that of patients without ADRs (11.9%). Among pediatric patients with ADRs the median (Q1-Q3) age was 29.5 (12-73.25) months. Most of ADRs were observed in infants and children (43.3% and 41.7%, respectively vs adolescents, 15%). In addition, in children with ADRs, females [41 (14-105)] were older than males [23 (11-45)] (p=0.044). Most adverse reactions were serious (75.8%) and 20.8% were preventable or probably preventable; however, the majority of serious ADRs (93.4%) resulted without sequelae. The reactions were found to be as probable (54.2%) or possible (45.8%). Vaccines (n=63), antibacterials (n=31) and anti-inflammatory medicines (n=14) were the most frequently drugs involved. Organ toxicity mapping due to vaccines was general disorders and administration site conditions (65.1%), nervous disorders (50.2%), cutaneous disorders (35%), followed by gastrointestinal disorders (20.6%). Cutaneous disorders (76%) gastrointestinal (20.7%), general (15.5%), and nervous disorders (8.6%) were the organ toxicity mapping due to drugs. Active pharmacovigilance has an essential role in supporting the development of strategies aimed at intervention to reduce admissions due to ADRs. Our data suggest that ADRs represent the first cause of hospitalization to the Pediatric Emergency Department. Furthermore, according to the literature, vaccines and antibiotics are the most frequent cause of adverse drug reactions in children.